Alternative Magnesium Sulfate Dosing Regimens for Women With Preeclampsia: A Population Pharmacokinetic Exposure-Response Modeling and Simulation Study - Lihong Du (2020)
© 2019 Meck Sharp & Dohme Corp. The Journal of Clinical Pharmacology published by Wiley Periodicals, Inc. on behalf of American College of Clinical Pharmacology Magnesium sulfate is the anticonvulsant of choice for eclampsia prophylaxis and treatment; however, the recommended dosing regimens are costly and cumbersome and can be administered only by skilled health professionals. The objectives of this study were to develop a robust exposure-response model for the relationship between serum magnesium exposure and eclampsia using data from large studies of women with preeclampsia who received magnesium sulfate, and to predict eclampsia probabilities for standard and alternative (shorter treatment duration and/or fewer intramuscular injections) regimens. Exposure-response modeling and simulation were applied to existing data. A total of 10 280 women with preeclampsia who received magnesium sulfate or placebo were evaluated. An existing population pharmacokinetic model was used to estimate individual serum magnesium exposure. Logistic regression was applied to quantify the serum magnesium area under the curve-eclampsia rate relationship. Our exposure-response model-estimated eclampsia rates were comparable to observed rates. Several alternative regimens predicted magnesium peak concentration < 3.5 mmol/L (empiric safety threshold) and eclampsia rate ≤ 0.7% (observed response threshold), including 4 g intravenously plus 10 g intramuscularly followed by either 8 g intramuscularly every 6 hours × 3 doses or 10 g intramuscularly every 8 hours × 2 doses and 10 g intramuscularly every 8 hours × 3 doses. Several alternative magnesium sulfate regimens with comparable model-predicted efficacy and safety were identified that merit evaluation in confirmatory clinical trials.